Symptomatic pelvic venous insufficiency: a review of the current controversies in pathophysiology, diagnosis, and management. Issue 6 (June 2022) - Barge, T.F.; Uberoi, R.
Abstract : Symptomatic pelvic venous insufficiency (PVI) is defined as chronic pelvic pain resulting from dilated pelvic veins. It is a controversial area, with ongoing debate surrounding the underlying aetiology of pain, as well as how best to investigate and manage these patients. Multiple distinct underlying pathophysiological processes have been implicated and can broadly be classified as primary venous reflux, normally involving the ovarian veins, and secondary venous obstruction, which may involve either the ovarian or internal iliac veins. Multiple terms have been used to describe this spectrum of conditions including pelvic congestion, May–Thurner and nutcracker syndromes; however, this terminology is imprecise and fails to define the underlying pathological process. A recent consensus classification of pelvic venous disorders aims to improve this nomenclature to aid clinical communication, decision-making, and future research. This is important as the treatment options differ according to the underlying cause. Imaging plays an essential role in the diagnostic process, both to define the underlying pathophysiology and to help plan treatments. Minimally invasive radiologically guided embolisation and/or venous stenting now form the mainstay of management with good reported outcomes. The present article discusses the proposed pathophysiology and aetiology of pain in PVI, reviews the role of imaging in the diagnosis, and considers the role of catheter-directed treatments. Highlights: Pelvic venous insufficiency is an under-recognised cause of chronic pelvic pain. Imaging plays an essential role in the diagnosis. Interventional radiology is the mainstay of treatment. We review the causes, recent classification system, diagnosis and treatment.